ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) DAN RETURN ON ASSETS (ROA) PADA PT. INDOCEMENT TUNGGAL PRAKARSA TBK - Danna, Sulfiani Elfreda (EKONOMIA, 2020)
Sulfiani : Analysis of financial performance using the method of Economic Value Added (EVA) and Return On Assets (ROA) at PT. Indocement Tunggal Prakarsa Tbk (under the guidance of Mrs. Elfreda Aplonia Lau as mentor I and Mrs. Danna Solihin as mentors II).               The purpose of this study is to analyze and study the growth of financial performance of PT. Indocement Tunggal Prakarsa Tbk with the method of Economic Value Added (EVA) and Return On Assets (ROA) in the period 2013-2017.                     The theoretical basis used in this study is financial management that focuses on the methods of Economic Value Added (EVA) and Return On Assets (ROA). Kasmir (2010: 5) explains that "Financial management is all activities related to the acquisition, funding, and management of assets with several overall objectives". The analytical tools used are Economic Value Added (EVA) and Return On Assets (ROA) and growth in Economic Value Added (EVA) and Return On Assets (ROA).               The results of this study indicate that the financial performance of PT. Indocement Tunggal Prakarsa Tbk is measured from 1) Economic Value Added (EVA) based on the calculation results of the 2013-2014 period experiencing growth, the hypothesis is accepted, the 2014-2015 period experiences a decline in growth, the hypothesis is accepted, the 2015-2016 period grows, the hypothesis is rejected and in the period 2016-2017 experienced a decline in growth, the hypothesis was accepted. 2) Return On Assets (ROA) based on the results of calculations in the 2013-2014 period experiencing growth then the hypothesis is accepted, the 2014-2015 period has decreased growth, the hypothesis is accepted, the period 2015-2016 has decreased growth, the hypothesis is accepted and the period 2016-2017 has decreased growth, the hypothesis is accepted.